1973
DOI: 10.1111/j.1440-1673.1973.tb01430.x
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Dissection Involving an Aberrant Right Subclavian Artery Studied by Aortography

Abstract: Summary A case is reported of an aberrant right subclavian artery detected at aortography following its involvement in a dissecting aneurysm commencing in the adjacent aortic arch, an example of a small group unrecognized until complicated by acquired disease. The clinical features are discussed briefly and the absence of tracheo‐oesophageal compression at any stage emphasized. Implication of the brachiocephalic branches is noted to be uncommon in such a distally originating aortic dissection. The aorto‐graphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…13 It was not until 1973 that Syme et al carried out the second descending aorta replacement for managing this pathology. 14 In 2008, a study of 452 patients by Wang et al revealed that the mortality rate of descending aorta replacement was 6.35% and the early incidence of postoperative complications was 11.1%. 15 High mortality and morbidity rates, as well as the trauma of left thoracic posterior-lateral incision, limit the application of descending aorta replacement for treating thoracic aortic disease.…”
Section: Discussionmentioning
confidence: 99%
“…13 It was not until 1973 that Syme et al carried out the second descending aorta replacement for managing this pathology. 14 In 2008, a study of 452 patients by Wang et al revealed that the mortality rate of descending aorta replacement was 6.35% and the early incidence of postoperative complications was 11.1%. 15 High mortality and morbidity rates, as well as the trauma of left thoracic posterior-lateral incision, limit the application of descending aorta replacement for treating thoracic aortic disease.…”
Section: Discussionmentioning
confidence: 99%